Distinctive climate signals in reanalysis of global ocean heat content. Issue 9 (10th May 2013) - Balmaseda, Magdalena A.; Trenberth, Kevin E.; Källén, Erland
<x xml:space="preserve">Abstract</x> [1] The elusive nature of the post‐2004 upper ocean warming has exposed uncertainties in the ocean's role in the Earth's energy budget and transient climate sensitivity. Here we present the time evolution of the global ocean heat content for 1958 through 2009 from a new observation‐based reanalysis of the ocean. Volcanic eruptions and El Niño events are identified as sharp cooling events punctuating a long‐term ocean warming trend, while heating continues during the recent upper‐ocean‐warming hiatus, but the heat is absorbed in the deeper ocean. In the last decade, about 30% of the warming has occurred below 700 m, contributing significantly to an acceleration of the warming trend. The warming below 700 m remains even when the Argo observing system is withdrawn although the trends are reduced. Sensitivity experiments illustrate that surface wind variability is largely responsible for the changing ocean heat vertical distribution.